Brunner gland hyperplasia of duodenum: A rare case mimicking malignancy with obstruction - Kumar, P Bharath; Gupta, Arnab; Madhabathula, Santhosh; Bhattacharya, Samir (Indian Journal of Case Reports, 2018)
An extremely uncommon benign tumor of duodenum, Brunner gland hyperplasia (BGH), is hereby reported in a 51-year-old male, who presented with recurrent vomiting and epigastric discomfort. Upper gastrointestinal endoscopy, computed tomography scan abdomen, and clinical presentation were suspicious of a malignant tumor with gastric outlet obstructive symptoms, and hence, pancreaticoduodenectomy was done. Post-operative histopathological examination confirmed it to be BGH.